MicroRNA-125b suppresses the proliferation and osteogenic differentiation of human bone marrow-derived mesenchymal stem cells - CHEN, SHI; YANG, LIU; JIE, QIANG; LIN, YAN-SHUI; MENG, GUO-LIN; FAN, JIN-ZHU; ZHANG, JIN-KANG; FAN, JING; LUO, ZHUO-JING; LIU, JIAN (Molecular medicine reports, 2014)
The regressive biological function of human bone marrow-derived mesenchymal stem cells (hBMSCs) is one of the key factors resulting in the decrease of bone mass in senile osteoporosis. MicroRNAs (miRs) are non-coding small RNAs involved in various gene regulation processes. Whether any miR(s) are involved in the progression of osteoporosis by regulating the biological function of hBMSCs remains to be elucidated. The present study aimed to compare the expression levels of miR-125b in hBMSCs derived from senile osteoporotic patients with that of control (normal) subjects. A significantly upregulated expression of miR-125b in osteoporotic hBMSCs was detected. To elucidate the biological function of miR-125b in senile osteoporosis, the effects of miR-125b expression on proliferation and osteogenic differentiation of hBMSCs were assessed using gain- and loss-of-function studies. It was evident that the overexpression of a miR-125b mimic was able to suppress the proliferative and osteogenic differentiation of senile hBMSCs. In contrast, repression of the function of miR-125b by transfection of an miR-125b inhibitor promoted the proliferation and osteogenic differentiation of hBMSCs. Furthermore, the potential target gene of miR-125b, osterix (Osx), was examined. The results of the present study strongly suggested that miR-125b may regulate osteogenic differentiation of hBMSCs through the modulation of Osx expression.